Outcomes and Predictive Factors Associated with Adequacy of Antimicrobial Therapy in Patients with Central Line-Associated Bloodstream Infection - Yokota, Paula Kiyomi Onaga; Marra, Alexandre Rodrigues; Belucci, Talita Rantin; Victor, Elivane da Silva; Santos, Oscar Fernando Pavão dos; Edmond, Michael B. (Frontiers in Public Health, 2016)
Background Central venous catheters are significant risk factors for bloodstream infection (BSI), which are directly associated with increased morbidity and mortality. Methods This study was a retrospective cohort study for the time period of July 2011–June 2014 in patients with central line-associated bloodstream infection (CLABSI) to determine the microbiological profile and antimicrobial adequacy of patients with CLABSI in a tertiary hospital. Results One hundred and twenty-one CLABSI cases were identified. Ninety-two percent (n = 111) of patients had monomicrobial BSI. Gram-negative bacteria were the most prevalent (49%, n = 63), with Klebsiella spp. predominating (30%, n = 19). Among the Gram-positive bacteria (n = 43, 33%), coagulase-negative staphylococci was the major pathogen (58%, n = 25), and all isolates were methicillin resistant. Antimicrobial therapy was assessed as adequate in 81% (n = 98) of cases. In-hospital mortality was 36% (n = 43 cases). Conclusion Our CLABSI patients had a high mortality, although antimicrobial therapy was appropriate. Gram-negative bacteria were responsible for almost half of the cases and there was a high rate of bacteria resistance to extended-spectrum antibiotics.